Davidson's principles and practice of medicine - Penman, Ian D.; Ralston, Stuart H.; Strachan, Mark W.J; Hobson, Richard P. (Churchill Livingstone/Elsevier, 2022)
Well over two million medical students, doctors and other health professionals around the globe have owned a copy of Davidson's Principles and Practice of Medicine since it was first published over 70 years ago. Now in its 24th Edition, this thoroughly updated textbook describes the pathophysiology and clinical features of the most frequently encountered conditions in the major specialties of adult medicine, and explains how to recognise, investigate, diagnose and manage them. Taking its origins from Sir Stanley Davidson's much-admired lecture notes, Davidson's has endured because it keeps pace with how modern medicine is taught and provides a wealth of trusted information in an easy-to-read, concise and beautifully illustrated format.